1990
DOI: 10.1007/bf00294622
|View full text |Cite
|
Sign up to set email alerts
|

Meningovascular form of neuroborreliosis: similarities between neuropathological findings in a case of Lyme disease and those occurring in tertiary neurosyphilis

Abstract: Recent observations have delineated the neurological manifestations of Lyme disease, but, to our knowledge, no detailed neuropathological study from autopsy cases has been reported. In this report we describe the neuropathological findings in a case of Lyme neuroborreliosis. The chronic meningitis, the occlusive meningovascular and secondary parenchymal changes that we found are similar to those occurring in the meningovascular form of neurosyphilis. Thus, we suggest that the case described here represents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
6

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 16 publications
2
36
0
6
Order By: Relevance
“…The meningovascular lesions in our case arc compat ible with LNB pathology [11], In contrast the spongiform change in the cerebral cortex and thalamus has not been reported. The spongy areas were covered with numerous activated microglial cells and GFAP-positive astrocytes, and absence of neurons showing ischemic change ex cludes a possibility of systemic hypoxia.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The meningovascular lesions in our case arc compat ible with LNB pathology [11], In contrast the spongiform change in the cerebral cortex and thalamus has not been reported. The spongy areas were covered with numerous activated microglial cells and GFAP-positive astrocytes, and absence of neurons showing ischemic change ex cludes a possibility of systemic hypoxia.…”
Section: Discussionmentioning
confidence: 69%
“…Pachner et al [8] reported 6 patients with LNB and a brain biopsy specimen taken from 1 patient with chronic encephalopa thy demonstrated microglial nodules and silver-impreg nated organisms without any necrotic lesion or perivascu lar lymphocyte infiltration. Miklossy et al [11] demon strated a brain that showed meningitis and multiple isch emic lesions caused by occlusive vascular change with perivascular leukocyte infiltration, and they concluded that the parenchymal CNS lesions were ischemic infarcts due to occlusive vascular changes and meningitis, both of which were consistent with those in meningovascular forms of tertiary neurosyphilis. In a most recent study, Oksi et al [ 15] reported a necropsied brain infected con comitantly with thick-borne virus and B. burgdorferi, in which hemorrhagic necroses of the bilateral hippocampi, glial nodules and neuronal cell loss in the thalamus, cere bral cortex and spinal cord were found.…”
mentioning
confidence: 72%
“…obliterative inflammatory vasculopathy associated with spirochetes present in the leptomeninges, have been described as ‘a meningovascular form of neuroborreliosis’ [22]. In syphilis, obliterative endarteritis of the vasa vasorum of large arteries can lead to aneurysm formation [23].…”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestations of Lyme neuroborreliosis are headache, meningismus, or radiculopathic symptoms, whereas CNS parenchymal involvement is rare (Hansen and Lebech, 1992;Pacher et al, 1998a). The localization of spirochetes in the CNS of humans has been reported only in a handful of cases using nonspecific silver impregnation techniques (Kobayashi et al, 1997;Kuntzer et al, 1991;Miklossy et al, 1990). The positivity of the PCR-ELISA in samples from the cerebrum and brainstem likely represents leptomeningeal, rather than parenchymal, localization.…”
Section: Borrelia Burgdorferi In Immunosuppressed Macaca Mulattamentioning
confidence: 99%